Q. 54.3( 6 Votes )

If one zeros of t

Answer :

It is given in the question that,

One of the zero of the polynomial kx2 + 3x + k is 2


It will satisfy the above polynomial


Now, we have


k (2)2 + 3 (2) + k = 0


4k + 6 + k = 0


5k + 6 = 0


5k = - 6


k = -6/5


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses